Comparison of phenolic content, antioxidant capacity and anti-inflamatory activity of commercial herbal infusions - Muñoz-Velázquez, Erika Elizabeth; Rivas-Díaz, Karla; Loarca-Piña, Ma. Guadalupe Flavia; Mendoza-Díaz, Sandra; Reynoso-Camacho, Rosalía; Ramos-Gómez, Minerva (Revista Mexicana de Ciencias Agrícolas, 2018)
Actually there is an increase on infusion consumption due their beneficial properties, which are attributable to the presence of phenolic compounds. By this reason, the aim of this study was to assess phenolic content, antioxidant capacity and anti-inf lammatory capacity of commercial infusions of peppermint (Mentha piperita L.), lemon grass (Cymbopogon citratos), chamomile (Matricaria chamomilla L.), arnica (Heterotheca inuloides) and boldo (Peumus boldus Molina) obtained in supermarket in 2009. Phenols content and antioxidant capacity were defined by spectrophotometry techniques. Also, identification and quantification of phenolic compound was made by HPLC. The anti-inflammatory activity was assessed by inhibition of ciclooxigenasa-2 (COX-2) enzyme. Boldo infusion had greatest content of phenolic compounds and greater antioxidant capacity measured by ABT techniques, followed by chamomile infusions by FRAP method. In assessed infusions ten different compounds were identified, finding in higher concentration the compounds catechin, epigallocatechin gallate, rosmarinic acid and eriocitrin. As for inhibitory capacity on COX-2, chamomile and lemon samples had higher percentages of inhibition, followed by boldo infusion. In general, results suggest that boldo and peppermint commercial infusions show biological properties with potential benefits for health.
Keywords: Peumus boldus; Mentha piperita L.; Matricaria chamomilla L.; antioxidant capacity; COX-2 inhibition